FLORIONIM AND THEIR ARRIVALS IN PORTABLE MEANINGS COMMENTS ON TERMS - Nurmuratova Khilola Yashinovna, Khilola (Confrencea, 2023)
This article provides an overview of the meaning of a word, its semantic structure, as well as its basic meanings that represent certain concepts, and its subtle meanings that represent other facets of a word, its portable meanings, and the use of Florionim in a portable sense. В данной статье показана общая информация о значении слова, его семантические составляющие, также противоположное значение, его переносное значение и использование флорионимов в переносном значении. This article gives information about the meaning of the word and its semantic structure as well as essential meaning expressing specific notions and using florionyms in the context.